El hombre del rey : Robin Hood III - Donald, Angus, 1965-; Rodríguez de Lecea, Francisco; Donald, Angus, 1965- (Barcelona, España ; Buenos Aires, Argentina : Edhasa, 2012)
Entreated by a betrayed and imprisoned Richard the Lionheart to save England, Robin Hood, a renegade earl and former outlaw, embarks on a deadly mission at the side of loyal lieutenant Alan Dale in a heroic bid to restore the king to the throne.
Online resource; title from PDF title page (Digitalia, viewed June 23, 2015)
Keywords: Robin Hood (Legendary character) -- Fiction; Great Britain -- History -- Richard I, 1189-1199 -- Fiction; Electronic books